PELATIHAN PEMBUATAN BIBIT NATA (ACETOBACTER XYLINUM) DENGAN MENGGUNAKAN NANAS DAN KECAMBAH KACANG HIJAU DI INDUSTRI KERIPIK TEMPE DAN TEMPE di KAMPUNG SANAN KOTA MALANG - Devita Sari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
This training program aims to enable local communities to reproduce nata seeds (acetobacter xylinum) with ingredients that are safe for consumption. This nata seed is one of the important ingredients in making nata de soya that is being tried to be produced by the people of Kampung Sanan. Other ingredients are pineapple juice which naturally contains acetobacter xylinum and substitutes coconut water, and green bean sprouts as a source of nitrogen (one of the foods needed for the breeding of acetobacter xylinum). The method used is intensive training and mentoring for participants selected by the association. Evaluation is done by testing the nata seeds that have successfully grown to make nata de soya. Nata seedlings are said to be successful if a white layer (cellulose) grows on the surface of the bottle. Fermentation process for 7-10 days. The trainees made 15 bottles of nata seeds, which managed to form 10 bottles of cellulose on the surface, 5 of which failed because cellulose did not form. The conclusion is that pineapple juice and mung bean sprouts can be used as a breeding medium for acetobacter xylinum. The material is organic so it is safe for consumption, easy to obtain and inexpensive.